Development of hydraulic ram pump to determine the performance and efficiency - Danieil Wilson Sinin (2022)
This research focuses on creating a ram pump that will enable water pumping without the use of an external energy source. The waste valve and the delivery valve are the only two moving parts in a hydraulic ram pump, which is a straightforward device. There have been numerous studies done on the ram pump in the past. In this instance, the goal was to identify the optimal set of parameters to achieve the highest level of efficiency. The project will be conducted by studying scientific literature and performing experiments. The objective of this study was to test the effects of varying the length of drive pipe combined with the variation of the size for the ram pump towards the flow rate and efficiency of hydraulic ram pump. This study was conducted by using a pipe with the length varies from 3 meters, 4 meters and 5 meters for the drive pipe and two size of pump which are in size of ½ inch and ¾ inch. The results showed that ¾ inch of pump size with the length of drive pipe be 5 meters in length showed the highest flow rate of 2.05 liters per minute with overall efficiency of 64.27%.